2008
DOI: 10.1177/1081180x08092829
|View full text |Cite
|
Sign up to set email alerts
|

Information system needs in health promotion: a case study of the Safe Community programme using requirements engineering methods

Abstract: Objectives: To explore the need for information system support in health promotion programs. Results: Sharing of management information, creating social capital for safety promotion, and injury data recording were found to be key areas that need to be further supported by computer-based information systems in safety promotion practice. 90% (111/123) of the respondents reported having access to a personal computer workstation with standard office software. The interest in using more advanced computer applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Distribution of programme management information, at the right level of detail, has been reported to be difficult in the Safe Communities in Sweden. [ 34 ] The same study also reported a need for a group communication system that could be used to create inter-organizational trust among the organizations engaged in safety promotion. Politicians need continuous information in order to promote a programme.…”
Section: Discussionmentioning
confidence: 97%
“…Distribution of programme management information, at the right level of detail, has been reported to be difficult in the Safe Communities in Sweden. [ 34 ] The same study also reported a need for a group communication system that could be used to create inter-organizational trust among the organizations engaged in safety promotion. Politicians need continuous information in order to promote a programme.…”
Section: Discussionmentioning
confidence: 97%
“…Findings from this study highlight the interrelation between individual and organizational factors, tools and strategies that affect framing of health communication and, how health communication is communicated, received and understood. These factors need to be addressed by researchers and PHC actors in the planning and designing an ICT mediated health channel for health promotion [8,24], to achieve its goal of improving health literacy [4,14], and to realize the national public health goal of re-orienting health care services into a more health promoting services [18]. …”
Section: Discussionmentioning
confidence: 99%
“…In order to identify a common health promoting approach and strategies based on health promotion values and principles, a participatory design involving both end users and providers throughout the design process will be used. Participatory design is attributed to contribute to capacity building as participants learn with and from each other while working towards the same goal, making it an appropriate method for development of VHT [24,45]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Developers of technology for health often overlook important user-characteristics, tasks, preferences and usability concerns, resulting in systems that generate more confusion than benefits, or simply remain inadequate (Johnson et al, 2005;Timpka et al, 2008). As a result, health policy makers are now demanding evidence to justify investments in health information systems (Kushniruk and Patel, 2004).…”
Section: Usability Engineering and User-testingmentioning
confidence: 99%